Cytokines for the treatment of gastrointestinal cancers: clinical experience and new perspectives. (September 2013) - Hernandez-Alcoceba, Ruben; Sangro, Bruno; Berraondo, Pedro; Gonzalez-Aseguinolaza, Gloria; Prieto, Jesus
<x xml:space="preserve">Abstract</x> Introduction: Cytokines are key mediators of the immune system and have been proposed as therapeutic agents against cancer, either as recombinant proteins, or as transgenes in gene therapy approaches. Stimulation of immune responses against cancer cells is an appealing method to treat tumors with high risk of relapse and systemic dissemination. Areas covered: We provide a critical overview of clinical trials involving the use of cytokines for the treatment of liver, colon and pancreatic cancers. Special attention has been paid to advances in the field of gene therapy and oncolytic viruses. The potential of new developments still in a pre-clinical stage is also discussed. We have revised public sources of information (PubMed, US National Institutes of Health clinical trials database) up to January 2013. Expert opinion: The complexity of the immune system and the unfavorable pharmacokinetic properties of cytokines limit the efficacy of these molecules as single agents for the treatment of cancer. Expression from gene therapy vectors, together with new methods of targeting and stabilization, may overcome these hurdles. We believe cytokines will play a crucial role as part of combined approaches, enhancing the action of adoptive cell immunotherapy, oncolytic viruses or biological therapies.